Examining the Effects of SRSD in Combination with Video Self-Modeling on Writing by Third Grade Students with Learning Disabilities. Issue 2 (3rd April 2018) - Miller, Katie M.; Little, Mary E.
ABSTRACT: The purpose of this study was to determine the effectiveness of an instructional package, Self-Regulated Strategy Development, a cognitive strategy instructional model (POW + TREE), in combination with video self-modeling (VSM) on the improvement on the written expression of three third-grade students with learning disabilities (LD). This manuscript addresses the results of a multiple probe across participants, single-subject design, which data from various components of writing, including essay elements, length of responses, time, and overall writing quality were collected. All students who received the instructional package intervention improved their overall writing performance on opinion essays as measured by the number of opinion essay elements. During the maintenance phase of the intervention, students who received a VSM booster session retained their total number of opinion essay elements at mastery levels. Implications for students with LD, as well as future research considerations, will be discussed.